CALCULATION OF LIFTING FOUNDATION FOR SWELLING SOILS WATERSHED IN SUDAN - , СЕЙФ ЭЛЬДИН, А. Б., А. А., В. Г. (Municipal economy of cities. Series: «Economy science», 2013)
The method of calculation, using empirical relationships between key parameters of swelling and physical properties of soils. Provides examples of its use ..